Reproducibility and reliability of performance indicators to evaluate the therapeutic effectiveness of biofeedback therapy after elbow surgery: An observational case series. Issue 34 (21st August 2020) - Takahashi, Rina; Sano, Kazufumi; Kimura, Kazumasa; Ishioka, Toshiyuki; Suzuki, Makoto; Nakaya, Naoki; Ozeki, Satoru; Hamaguchi, Toyohiro
Abstract : Abstract: Electromyographic biofeedback (EMG-BF) therapy provides information on the state of contraction of the targeted muscles and relaxation of their antagonists, which can facilitate early active range of motion (RoM) after elbow surgery. Our aim in this study was to calculate the minimum detectable change (MDC) during EMG-BF therapy, initiated in the early postoperative period after elbow surgery. This study is an observational case series. EMG-BF of muscle contraction and relaxation was provided during active elbow flexion and extension exercises. Patients completed 3 sets of 10 trials each of flexion and extension over 4 weeks. The total range of flexion-extension motion and scores on the Japanese Society for Surgery of the Hand version of the disability of the arm, shoulder, and hand questionnaire and the Japanese version of the Patient-Rated Elbow Evaluation were obtained at baseline and weekly during the 4-week intervention period. A prediction formula was developed from the time-series data obtained during the intervention period, using the least-squares method. The estimated value was calculated by removing the slope from the prediction formula and adding the initial scores to residuals between the measured scores and predicted scores individually. Systematic error, MDC at the 95th percentile cutoff (MDC95 ), repeatability of the measures, and the change from the baseline to each time-point of intervention were assessed. The MDC95 was obtained for all 3 outcome measures and the range of values was as follows: RoM, 8.3° to 22.5°; Japanese version of the Patient-Rated Elbow Evaluation score, 17.6 to 30.6 points; and disability of the arm, shoulder, and hand questionnaire subscale: disability and symptoms score, 14.2 to 22.9 points. The efficacy of EMG-BF after elbow surgery was reflected in earlier initiation of elbow RoM after surgery and improvement in patient-reported upper limb function scores. The calculated MDC95 cut-offs could be used as reference values to assess the therapeutic effects of EMG-BF in individuals. Abstract : Supplemental Digital Content is available in the text